(untitled) (Czech Journal of International Relations, 1992)
Presently, Hungary is finished with the first stage of adaptation of its political and economic systems to the needs of Western European countries, with the most important change being its involvement with the EC. In the sphere of international relations, it reflects the acceptance of Hungary in to the Council of Europe as well as into negotiations on association agreements. The attachment of the country to these processes is conditioned by a number of international political and economic circumstances. At present, economic advances are taking place in Hungary, which should give it a more hopeful economic future. Hungary has comparative advantages over Czechoslovakia and Poland due to a more stable economic and intrapolitical developments. The prepared association agreement will not remove the danger that Hungary, together with other Central European counties, will remain on the periphery of the multispeed continental integration process.